Weed seed predation rate in cereals as a function of seed density and patch size, under high predation pressure by rodents. (30th December 2013) - Daedlow, D; Westerman, P R; Baraibar, B; Rouphael, S; Gerowitt, B; Liebman, Matt
Summary Weed seed predation is an ecosystem service, influencing weed population dynamics. The impact of weed seed predation on weed population dynamics depends on how predators respond to seed patches at the field scale. Seed predation will be most effective if the proportion of seeds predated increases with increasing size and seed density of patches. Density‐dependent rodent seed predation was measured by varying seed density and patch size in four irrigated conventionally managed cereal fields in north eastern Spain. Artificial weed seed patches were created by applying a range of Lolium multiflorum seed densities from 0 to 7500 seeds m−2 in 225 m2 patches (2008) or in patches that varied in size from 1 to 9 m2 (2009). Seed predation was estimated using seed cards and seed frames. The granivorous rodents Mus spretus and Apodemus sylvaticus caused high seed predation rates (92%) in three fields, whereas in a fourth field, it was lower (47%). Rodents responded in an inversely density‐dependent manner, but this had little biological meaning as even in patches seeded with the highest density, the input to the soil seedbank was reduced by 88%. For the period of time this experiment lasted, hardly any new seeds would have entered the seedbank.